The repercussions of Chronic Obstructive Pulmonary Disease for public health (Research, Society and Development, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is characterized by airflow restriction that is not fully reversible. It is a common, recurrent condition and cause of significant morbidity and mortality. However, underdiagnosis still prevails in clinical practice. The following article aimed to describe, through a narrative review of the literature, a broad approach to chronic obstructive pulmonary disease. The results of this study clarified in a very concrete way the definition, classification and diagnostic criteria of the disease, highlighting the etiologies and implications of smoking. Clinical and social aspects, application of complementary exams and therapeutic options were grouped. Conclusively, it is clarified that COPD is a lung disease with intense repercussions for public health. More in-depth studies and research are essential to overcome the delay in diagnosis and typical clinical manifestations of the disease.